Crystal structure of (E)-2-hydroxy-N′-(1-(4-hydroxyphenyl)propylidene)benzohydrazide, C16H16N2O3 - Xu Xiaona; Tong Hongjuan; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C16H16N2O3, monoclinic, P21/c (no. 14), a = 8.9406(3) Å, b = 9.3999(3) Å, c = 17.1101(6) Å, β = 98.8190(10)°, V = 1420.95(8) Å3, Z = 4, Rgt(F) = 0.0468, wRref(F2) = 0.1213, T = 298 K.